Tinjauan Yuridis Tentang Proses Penyelesaian Perkara Perceraian ( Studi Kasus Di Pengadilan Negeri Surakarta ) - Gunawan, Totok; , Nuswardhani, S.H.,S.U (2017)
The purpose of this study is to determine how the settlement process of a divorce case, to determine the consideration of the judge in deciding the case of divorce, to determine the legal consequences arising from a divorce case. This study uses normative approach and using a qualitative approach. Descriptive study. Data analysis methods used by the author is a qualitative approach. In the process of the settlement of divorce cases in the District Court begins by filing a lawsuit of divorce for religious non-Islamic to the District Court, then wait for the call of the party by the District Court to conduct a hearing divorce cases in accordance with the time specified by the District Court and the pihakpun dating to the Court State, Justice started hearing the divorce case with the reading of a lawsuit by the judge continued response from the defendant, then continued replik plaintiff and defendant duplik agenda continued with the evidence, after verification is complete, the plaintiff and the defendant to make conclusions, after which the verdict of the judge read out. As a result of the law in the aftermath of divorce on the relationship of husband and wife can be seen in this case that after the divorce, the legal relationship between husband and wife really had broken up and they get a new status, a widower for a husband and wife designation for the widow. In this case there are also legal consequences of the parenting of the couple husband and wife. In this case of course the child of the couple will be in the care of her mother.